2018
DOI: 10.1016/j.geoderma.2018.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Sub-micrometer distribution of Fe oxides and organic matter in Podzol horizons

Abstract: The spatial distribution of soil constituents at the micrometer scale is of great importance to understand processes controlling the formation of micro-aggregates and the stabilization of organic carbon. Here, the spatial distribution of organic and mineral constituents in Podzol horizons is studied by concerted measurements of (i) the content of various forms of Fe, Al, Si and C determined by selective extraction in the fine earth fraction of soil (f < 2 mm); (ii) the elemental composition of the clay fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“…Fe is systematically closely associated with the organic crust at the surface of quartz grains as revealed by the concomitant presence of Fe and C (and also Al) in EDX elemental maps (Fig. 2), and as previously shown (Cornelis et al, 2018). The reductive dissolution of Fe(III) in these Fe coatings may thus affect associated OC.…”
Section: Characterization Of Fe and C Poolssupporting
confidence: 76%
See 1 more Smart Citation
“…Fe is systematically closely associated with the organic crust at the surface of quartz grains as revealed by the concomitant presence of Fe and C (and also Al) in EDX elemental maps (Fig. 2), and as previously shown (Cornelis et al, 2018). The reductive dissolution of Fe(III) in these Fe coatings may thus affect associated OC.…”
Section: Characterization Of Fe and C Poolssupporting
confidence: 76%
“…The inaccessibility of Fe(III) phases to Fe reducing bacteria has been invoked in riverine sediment settings to explain the discrepancy between the extent of (i) microbial Fe(III) reduction and (ii) reductive extraction by ascorbate (Hyacinthe et al, 2006). In this respect, Cornelis et al (2018) highlighted a mutual protection mechanism involving Fe protection within Fe-OMA as well as OM protection through coprecipitation and/or adsorption. DOC oxidation to CO 2 or HCO 3 − during DIR reactions might also explain the limited DOC release after S. putrefaciens addition.…”
Section: Influence Of Microbial Fe(iii) Reduction On Om Releasementioning
confidence: 99%
“…This is in contrast to Vermeire et al (2019), who reported increasing accumulation of Fe d in subsoils of a Podzol chronosequence. Overall, Fe d contents were at least one order of magnitude lower than in other sandy Podzols (Egli et al 2001;Mokma et al 2004;Cornelis et al 2018), indicating that for our case the parent material was generally very low in Fe.…”
Section: Soil Properties and Profile Characterisationcontrasting
confidence: 60%
“…Re‐oxidation of this Fe II is often rapid when it encounters molecular oxygen, generating Fe‐OC associations when DOC is present (Chen & Thompson, 2018). A large fraction of Fe‐associated C appears to consist of organo‐Fe coprecipitates with high molar C/Fe ratios (Wagai & Mayer, 2007; Zhao et al., 2016), but in many cases these contain Fe (oxyhydr)oxide phases buried within an organic matrix, which may not necessarily provide protection against OM oxidation (Cornelis et al., 2018; Kleber et al., 2015). Furthermore, Mössbauer spectroscopic analyses suggest that only a small fraction of the Fe III formed during redox cycling is likely to occur strictly in organo‐Fe III complexes in upland soils (Chen et al., 2020; Hall et al., 2018), especially given that much of the Fe II oxidation is catalyzed by mineral surfaces (Chen & Thompson, 2021).…”
Section: Resultsmentioning
confidence: 99%